Angiomyoma – A requisite in differential diagnosis of palatal growths - Pandya, Maitreyi; Rao, Dhanya S.; Mamatha, G. P.; Annigeri, Rajeshwari G. (International Journal of Health Sciences, 2019)
Vascular variant of leiomyomas termed angioleiomyomas rarely present in the oral cavity. They present themselves as well-circumscribed, slow-growing, superficial lesions covered by normal mucosa and sometimes bluish or purple in color. Clinicians often tend to overlook this entity due to the rarity and asymptomatic nature of the lesion. Scrupulous knowledge of this entity and a thorough examination is of value, as the lesion can impersonate or transform to malignancy, as a malignant counterpart exists. We present a case of angiomyoma of hard palate in a 46-year-old patient with a detailed review.